2017
DOI: 10.1016/j.rbmo.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response to 150 µg corifollitropin alfa in a GnRH-antagonist multiple-dose protocol: a prospective cohort study

Abstract: The incidence of low (<6 oocytes) and high (>18 oocytes) ovarian response to 150 µg corifollitropin alfa in relation to anti-Müllerian hormone (AMH) and other biomarkers was studied in a multi-centre (n = 5), multi-national, prospective, investigator-initiated, observational cohort study. Infertile women (n = 212), body weight >60 kg, underwent controlled ovarian stimulation in a gonadotrophin-releasing hormone-antagonist multiple-dose protocol. Demographic, sonographic and endocrine parameters were prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to analyse the ability of the automated Elecsys® AMH assay to predict ovarian response in a CFA antagonist protocol. The AUC for the prediction of low ovarian response in this study was 0.883, which is in line with previous studies reporting AUCs between 0.836 and 0.929 with other assays (Oehninger et al, 2015;Lerman et al, 2017;Baker et al, 2018;Scheinhardt et al, 2018;Jacobs et al, 2019). Similarly, the AUC for the prediction of high ovarian response was 0.865, which is in line with previous reports varying between 0.821 and 0.890 (Polyzos, et al, 2013;Oehninger et al, 2015;Lerman et al, 2017;Scheinhardt et al, 2018;Anckaert et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first study to analyse the ability of the automated Elecsys® AMH assay to predict ovarian response in a CFA antagonist protocol. The AUC for the prediction of low ovarian response in this study was 0.883, which is in line with previous studies reporting AUCs between 0.836 and 0.929 with other assays (Oehninger et al, 2015;Lerman et al, 2017;Baker et al, 2018;Scheinhardt et al, 2018;Jacobs et al, 2019). Similarly, the AUC for the prediction of high ovarian response was 0.865, which is in line with previous reports varying between 0.821 and 0.890 (Polyzos, et al, 2013;Oehninger et al, 2015;Lerman et al, 2017;Scheinhardt et al, 2018;Anckaert et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding AMH optimal cut-off levels for the prediction of the extremes of ovarian response, the cut-off of 1.0 ng/ ml, identified as the value with maximal sensitivity and specificity for predicting low response, seems to be comparable with previous studies and close to the proposed cut-offs defined by the Bologna criteria (Ferraretti et al, 2011). Baker et al (2018) reported a cut-off of 0.93 ng/ml in the prediction of four or fewer oocytes retrieved, whereas Lerman et al (2017) and Oehninger et al (2015) described a cut-off of 0.91 ng/ml and 1.03 ng/ml, respectively, as the most accurate to predict six or fewer oocytes retrieved.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations